A multi-centre study of adults with learning disabilities referred to services for antisocial or offending behaviour: demographic, individual, offending and service characteristics - Carson, Derek (Journal of learning disabilities and offending behaviour, 2010)
This study was carried out as part of a larger study commissioned by the UK Department of Health to investigate the service pathways for offenders with learning disabilities (LD). The study covered three health regions in the UK and included 477 people with LD referred to services because of antisocial or offending behaviour during a 12-month period. Data were collected concerning demographic, individual, offending behaviour and service characteristics. The findings of the study are broadly consistent with contemporary research concerning this population, particularly in relation to the nature and frequency of offending, history of offending, psychopathology, age and gender distribution. However, very few of those referred had any form of structured care plan, despite having significant offending histories, and this may have compromised early identification of their needs and communication between the health, social and other services involved